A Pattern of Tolerance Values Transformation by Parents Towards Early Childhood - Sumadi, Tjipto; Abdillah, Fauzi; Casmana, Asep Rudi (Frontiers in Education, 2021)
This study aims to discover a pattern of transformation of tolerance values from parents to early childhood. The tolerance value in this days and ages experience some problems in the context of nationality. It can be seen from some part of area in Indonesia. For instance, in the traditional village of Cigugur, life based on tolerance is experienced in the community. This study focused on the pattern of the Cigugur community in applying tolerance values in family and community life. This study uses a qualitative method to undertake the study. The data collection was carried out by observations and in-depth interviews, then it was verified and validated through four stages; which were member check, audit trial, triangulation, and expert opinion. Expert opinions were Cigugur religious leaders and indigenous people who were harvested in a group discussion forum. It can be concluded that the pattern of transformation of tolerance values from parents to early childhood could be transformed through some stages; (1) making sense of kinship as an adhesive between followers of different religions, (2) conveying religious teachings towards differences, not to be contested but to be respected and admired, (3) avoiding the content of certain political interests, (4) having a sense compassion for each other, and (5) doing tepo seliro (respect) do each other.